2014
DOI: 10.4236/jpee.2014.29016
|View full text |Cite
|
Sign up to set email alerts
|

Propagation Characteristics of Partial Discharge Pulses in the Cable

Abstract: In order to determine the type and location of partial discharge in cable, the effect of partial discharge (PD) pulse propagation in the cable is studied. Firstly, pulses are injected to cables of different lengths so that input and output signal can be measured at both ends of each cable. Then the transfer function of pulse propagation path can be defined. Secondly, high-voltage test is done in the cable joint with man-made defects, and typical PD waveforms are gotten. Seven parameters of waveform characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The equivalent timefrequency classification algorithm of the PD pulse was chosen to identify the deterioration degree. Different timefrequency features of PD waveforms at different deterioration stages provided a foundation for the identification of the deterioration degree of electrical trees [28,29].…”
Section: Waveform Characteristics Of Pdmentioning
confidence: 99%
“…The equivalent timefrequency classification algorithm of the PD pulse was chosen to identify the deterioration degree. Different timefrequency features of PD waveforms at different deterioration stages provided a foundation for the identification of the deterioration degree of electrical trees [28,29].…”
Section: Waveform Characteristics Of Pdmentioning
confidence: 99%
“…Generally, individual PD pulses under AC stresses are characterized by double exponential or Gaussian functions that have time characteristics on the range of hundreds of picoseconds to hundreds of nanoseconds [7,8]. Consequently, the PD pulses of AC stresses have frequency components on the range of MHz to GHz [9,10]. Although DC PD pulse analysis has been a rare research topic, in recent years, researchers have increasingly reported their studies on individual PD waveforms under DC stresses [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, IEC standard 60270 recommended the application of high bandwidth instruments including oscilloscopes in combination with appropriate coupling sensors to measure the waveform or frequency spectrums of PD pulses [19]. Recently, the high frequency current transformer (HFCT) and non-conventional high-frequency coupling antennas that operate on the range of UHF have been increasingly used for measuring PDs in AC systems owing to their advantages such as superior sensitivity, broad frequency range and reduced external noise [8,9,17,20]. The UHF antennas that analyze PD pulses by capturing their EM fields are good alternatives of conventional PD detection sensors.…”
Section: Introductionmentioning
confidence: 99%